Convicting the innocent : where criminal prosecutions go wrong - Garrett, Brandon (Cambridge, Mass. : Harvard University Press, 2011)
DNA exonerations have shattered confidence in the criminal justice system by exposing how often we have convicted the innocent and let the guilty walk free. In this unsettling in-depth analysis, Brandon Garrett examines what went wrong in the cases of the first 250 wrongfully convicted people to be exonerated by DNA testing. Based on trial transcripts, Garrett's investigation reveals larger patterns of incompetence, abuse, and error. Evidence corrupted by suggestive eyewitness procedures, coercive interrogations, unsound and unreliable forensics, shoddy investigative practices, cognitive bias, and poor lawyering illustrates the weaknesses built into our current criminal justice system. Garrett proposes practical reforms that rely more on documented, recorded, and audited evidence, and less on fallible human memory. Few crimes committed in the United States involve biological evidence that can be DNA-tested. How many unjust convictions are there that we will never discover? Convicting the Innocent makes a powerful case for systemic reforms to improve the accuracy of all criminal cases.--From publisher description.
Contaminated confessions -- Eyewitness misidentifications -- Flawed forensics -- Trial by liar -- Innocence on trial -- Judging innocence -- Exoneration -- Reforming the criminal justice system.
Includes bibliographical references and index.
Keywords: Judicial error -- United States; Evidence, Criminal -- United States; Post-conviction remedies -- United States